ANALISIS PENYEBAB DAN PENGENDALIAN KEJADIAN KECELAKAAN KERJA DI JALAN RAYA PADA DELIVERYMAN TAHUN 2014-2015 (STUDI KASUS PADA DELIVERYMAN PT. COCA COLA AMATIL INDONESIA CENTRAL JAVA) - Zhagita Puspa Trisna Lautama F.; Siswi Jayanti; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2016)
Deliveryman are driver who deliver product from producent to consument who have a high risk of work accidents on the highway. There is an increase in cases of work accidents on the highway in 2014-2015, eventhough the deliveryman is equipped with driver training and BAROMETER program. This study was conducted to analyze the causes of accidents on motorways and control efforts that have been made to control workplace accidents on the highway on a deliveryman PT. Coca Cola Amatil Indonesia Central Java. This research is a descriptive qualitative research. This study population of 5 people. The results showed there were three causes of accidents on the highway on a deliveryman PT. Coca Cola Amatil Indonesia Central Java in 2014-2015 that is substandard act of dangerous behavior, occupational factors and vehicle factors. Dangerous behavior in question is a lack of concentration when driving that causes deliveryman crashed into another rider, and lack of other riders so it hit a truck delivery. Areas of work in question is the number of delivery within one day exceed the limits of normal working hours, and the factor of the vehicle in question is a mismatch the application of inspection procedures check BAROMETER. Control is done is riding a defensive driving safety training, briefing and medical checkup. Suggestions for the company is implementing K3 well during the working process. As for the workers obey signs and traffic rules, comply with applicable K3 program, do a complete inspection to check BAROMETER, following the briefing and conduct in accordance with the loading capacity.